Green synthesis of ultrathin 2D nanoplatelets, hematene and magnetene, from mineral ores in water, with strong optical limiting performance. Issue 9 (15th February 2023) - Koutsioukis, Apostolos; Florakis, Georgios; Samartzis, Nikolaos; Yannopoulos, Spyros N.; Stavrou, Michalis; Theodoropoulou, Dionysia; Chazapis, Nikolaos; Couris, Stelios; Kolokithas-Ntoukas, Argiris; Asimakopoulos, Georgios; Gournis, Dimitrios P.; Tzitzios, Vasileios; et al.
Abstract : Hematene and magnetene nanoplatelets have been produced by liquid phase exfoliation of natural mineral ores, in a water solution of melamine under mild sonication. Abstract : Following the long-standing use of the liquid exfoliation of graphite for the production of graphene, a number of analogous van der Waals 2D nanomaterials have been also produced and studied extensively for several applications. Recently, liquid exfoliation has also been applied to isolate non-van der Waals 2D nanostructures. Here, we describe a green procedure for the liquid exfoliation of natural hematite and magnetite – natural iron ores – obtained from the Greek territory. Natural iron ores were exfoliated in a solution of melamine in water under mild sonication. The ultrathin exfoliated nanoplatelets, hematene and magnetene, respectively, form stable dispersions in pure water and have been extensively characterized by spectroscopic and microscopic techniques. Optical limiting experiments reveal the efficiency of the present non-van der Waals 2D nanomaterials, rendering them highly attractive for several applications in opto-electronics and photonics.